Hodgkin's disease in a patient with sarcoidosis. - Silva, G N (1996)
We present the case of a 37 years old woman with mediastinal lymphadenopathy since the age of 13. At de age of 14, the patient presented a left cervical lymphadenopathy and the onset of episodic nodose erythema. One year later, histological examinations of an enlarged lymph node revealed sarcoidal granulomata. Corticotherapy was prescribed and the patient became asymptomatic. At the age of 31, the patient complained of asthenia and fever with left parotid tumefaction. Corticotherapy was therefore resumed with good response. Three years later, the patient presented left parotid tumefaction, left cervical lymphadenopathy and painful eye congestion. The patient was submitted to parotidectomy and lymphadenectomy. One month later, an ulceration with progressive enlargement developed in the surgical scar, and the patient suffered from asthenia, anorexia, weight loss, fever, nocturnal sweating and cervical and axillary lymphadenopathy. At Santa Maria Hospital, the patient's condition was diagnosed as Hodgkin's disease, mixed cellularity subtype, stage II Bb with local cutaneous involvement. The prescribed treatment was MOPP/ABV-8 cycles- and complete remission was achieved. The patient is still asymptomatic after a follow-up of 6 years. Cutaneous involvement in Hodgkin's disease is rare and generally associated with advanced disease and poor prognosis, facts that did not occur in this case. The differential diagnosis between sarcoidosis and sarcoid reaction in Hodgkin's disease, the accidental coexistence of both entities and the evolution of sarcoidosis into lymphoma are also discussed. The sarcoidosis immune defect may be the result of the same immune disorder. No relationships between sarcoidosis and cutaneous involvement in Hodgkin's disease were found in the literature.